2007
DOI: 10.1002/ccd.21106
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of drug‐eluting stent restenosis with the same versus different drug‐eluting stent

Abstract: Reimplantation of DES for the treatment of DES ISR (same or different) is safe but associated with a high rate of recurrences at 1 year regardless of the initial DES type. Other treatment modalities for ISR of DES should be considered to further improve the overall TVR-MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 75 publications
3
51
0
2
Order By: Relevance
“…[33][34][35] Because there is currently no effective recommended treatment for such cases, simple balloon dilatation of restenotic tissue could be a major treatment strategy. Therefore, we examined the response to BA of vessels in ISR lesions based on OCT.…”
Section: Response To Ba In Isr Lesionsmentioning
confidence: 99%
“…[33][34][35] Because there is currently no effective recommended treatment for such cases, simple balloon dilatation of restenotic tissue could be a major treatment strategy. Therefore, we examined the response to BA of vessels in ISR lesions based on OCT.…”
Section: Response To Ba In Isr Lesionsmentioning
confidence: 99%
“…However, in the present study, lesion complexity, including quantitative coronary angiography results, was not less than that in previous registries. [4][5][6][7][8] Furthermore, routine angiographic follow-up might be associated with a higher incidence of focal restenosis. However, clinical presentation at follow-up angiography in the present study did not differ between patients with focal and non-focal restenosis.…”
Section: Angiographic Restenosis Pattern After Des Implantationmentioning
confidence: 99%
“…1-10 Large-scale randomized trials 1-3 have demonstrated a high proportion of focal restenosis after DES implantation, but on the other hand, recent real-world registries have shown that a significant proportion of restenosis is non-focal when DES are used in unselected lesions. [4][5][6][7][8] The present study evaluated angiographic patterns of restenosis after sirolimuseluting stent (SES) implantation in real-world practice in Japan. …”
mentioning
confidence: 99%
“…However, this hypothesis has not been proved in clinical observation. Garg et al (2007), Cosgrave et al (2007b), and Sardella et al (2009) reported, respectively, a similar prognosis between homo-DES and hetero-DES strategies in the treatment of DES-ISR. In our study, there was a trend toward lower MACE rates in the DES-ISR patients using a different type of DES, but it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 67%